Strategy To Improve The Performance Of Creative Industries SMEs Through The Development Of Innovation In The Field Of Marketing, Finance And Human Resources At SMEs Pasuruan - Diana Dwi Kusumasari; Bachtiar Wijaya; Sudarmiatin; Trisetia Wijijayanti (Abadi Institute, 2026)
This study aims to analyze innovation development strategies in the field of marketing, finance, and Human Resources (HR) as an effort to improve the performance of creative industry SMEs in Pasuruan. The background of this study is based on the phenomenon that although the creative industry sector contributes significantly to the regional economy, many MSMEs still face obstacles in digitizing marketing, financial management, and Human Resource Capacity Development. This study uses a descriptive qualitative approach to data collection techniques through in-depth interviews, field observations, and documentation. Informants of the study consisted of creative UMKM actors, officials of Pasuruan City Cooperatives and UMKM offices, as well as local business actors. The Data were analyzed using the Miles, Huberman & SaldañA (2018) interactive analysis model, which includes the stages of data reduction, data presentation, and conclusion. The results show that marketing innovation through digital strategies and creative branding is able to expand market reach, while financial digitization increases business efficiency and transparency. On the other hand, the development of creative human resources is a major driving factor in encouraging innovation and business sustainability. The synergy of the three aspects of innovation proved to be more effective in increasing productivity, turnover, and competitiveness of MSMEs compared to the implementation of some innovations.